2019
DOI: 10.3109/13668250.2019.1592126
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility, factor structure and construct validity of the easy-read Adult Social Care Outcomes Toolkit (ASCOT-ER)

Abstract: Background: The ASCOT-ER is an adapted easy-read version of the ASCOT-SCT4, a self-report measure of social care-related quality of life (SCRQoL) for social care evaluation. In this study, we investigated the instrument's feasibility, construct validity and factor structure. Method: Data were collected from 264 service users in England. Feasibility was evaluated by missing data and help to complete the questionnaire. Scale dimensionality was assessed using exploratory factor analysis. Construct validity was ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 56 publications
2
16
0
Order By: Relevance
“…215,216 Most tools use variations or extensions of mild, moderate and severe to label the severity of the condition. For example, the GAI is scored using the categories low anxiety (0-21), moderate anxiety (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) and potentially concerning levels of anxiety (> 36), and the MADRS uses the categories normal (0-6), mild depression (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19), moderate depression (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) and severe depression (> 34). As demonstrated in these two examples, some tools assume the presence of either condition, whereas others, including all those designed to screen, allow for a score that reflects 'no' or 'normal' levels of anxiety or depression.…”
Section: Anxiety and Depression Tools Rapid Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…215,216 Most tools use variations or extensions of mild, moderate and severe to label the severity of the condition. For example, the GAI is scored using the categories low anxiety (0-21), moderate anxiety (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) and potentially concerning levels of anxiety (> 36), and the MADRS uses the categories normal (0-6), mild depression (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19), moderate depression (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) and severe depression (> 34). As demonstrated in these two examples, some tools assume the presence of either condition, whereas others, including all those designed to screen, allow for a score that reflects 'no' or 'normal' levels of anxiety or depression.…”
Section: Anxiety and Depression Tools Rapid Reviewmentioning
confidence: 99%
“…Psychometric testing has consistently revealed that ASCOT has acceptable internal reliability. 13,15 Research with a wide range of social care user populations, including older adults, younger adults and adults with physical and sensory impairments, has established its validity, feasibility and reliability. 13,15,16 Expected SCRQoL, which is still relatively uncommon in quality-of-life research, has been shown to be a reliable indicator of social care need, as it is highly correlated with functional ability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, assessments that include picture-based options have been found to be more engaging and accessible than purely text-based measures for young children and individuals with intellectual disabilities. [13][14][15][16] Therefore, picture-based measures may also allow diverse autistic individuals, including people with cooccurring intellectual disabilities and people who do not speak or read, to participate in research and educational evaluations. Picture-based strategies such as photovoice and Talking Mats are increasingly (although still rarely) used to assess the firstperson perspectives of autistic people with diverse communicative capacities.…”
mentioning
confidence: 99%
“…1 There also needs to be caution and robustness against potential sources of bias. 2 1 A report of the adaptation of the ASCOT in easy-read format and its acceptability and feasibility for personal outcomes data collection in adults with intellectual and developmental disabilities is provided in Turnpenny et al (2018) and Rand et al (2019). 2 The issues of potential bias related proxy response and/or help to complete the questionnaire in the adult social care survey (ASCS) is discussed in Rand and Malley (2017).…”
mentioning
confidence: 99%